Family Role in Shaping Character Islam in Early Childhood Through Habituation Method - Khambali Khambali (Pusat Penerbitan Universitas (P2U) Unisba, 2017)
AbstractOne of the indicators of success in educating children of Muslim families is if the characters are owned by the child, especially early childhood by the values of Islam. An educational method to be applied is habituation. The results of this research were 1) the factors that influence the formation of character early childhood can be categorized into four ways, namely: (a) the first educational environment, the family is represented by parents, (b) family life seen from various aspects, socioeconomic status, as well as family life philosophy, (c) family upbringing, and (d) the activities based on common religious parents by involving early childhood; and 2) habituation is done early childhood with parents can be categorized into 2, namely: (a) habituation greeting, such as greetings, and others; and (b) habituation is shown in deeds, such as: leaving the flurry of activity when he heard the call to prayer, and others.Keywords: Family, Character Islami, Early Childhood, and Methods of Habituation.Abstrak Salah satu indikator keberhasilan keluarga muslim dalam mendidik anak adalah jika karakter yang dimiliki oleh anak sesuai dengan nila-nilai Islam. Metode pendidikan yang hendak diterapkan dengan metode pembiasaan. Hasil dari penelitian ini adalah 1) Faktor-faktor yang berpengaruh terhadap pembentukan karakter anak usia dini dapat dikategorikan menjadi 4 (empat) hal, yaitu: (a) lingkungan pendidikan yang pertama, yaitu keluarga yang diwakilkan oleh orang tua, (b) kehidupan keluarga yang dilihat dari berbagai aspek, baik status sosial ekonomi, filsafat hidup keluarga, maupun pola hidup keluarga, (c) pola asuh keluarga, dan (d) kegiatan-kegiatan yang berbasis keagamaan yang biasa dilakukan orang tua dengan melibatkan anak usia dini didalamnya; dan 2) Pembiasaan yang dilakukan anak usia dini bersama orang tua dapat dikategorikan menjadi 2 (dua), yaitu: (a) pembiasaan ucapan, seperti mengucapkan salam, dan lain-lain; dan (b) pembiasaan yang ditampilkan dalam perbuatan, seperti: meninggalkan segala aktivitas ketika mendengar adzan, dan lain-lain.Kata Kunci: Keluarga, Karakter Islami, Anak Usia Dini, dan Metode Pembiasaan.